(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The objectives of the Kingdom of Saudi Arabia’s Vision 2030 provide great and continuous support for discovering and nurturing talents in all priority development disciplines, which believe in the importance of investing in nurturing talents and innovators as they are the most important tributary to the prosperity of nations and are capable of shaping new future horizons to serve society. This research paper aims to identify the concept of talents with autism spectrum disorder, and to know the distinctive characteristics, methods and ways of detecting talents with autism spectrum disorder, and to identify methods of caring for talents with autism spectrum disorder. The importance of this research paper also lies in directing the attention of specialists in the field of special education to the importance of the category of talents with autism spectrum disorder and that they have talents in many fields. This research paper can contribute to caring for the category of talents with autism spectrum disorder and refining their talents. Through what the researcher has reached in the subject of caring for gifted people with autism spectrum disorder, it has become clear that studies that have addressed this category are rare. In many cases of diagnoses associated with autism spectrum disorder and accompanying disabilities, the gifted category stands out, which is considered a category of double exceptionality. Therefore, the methods of detection, identification and care differ radically in terms of services, methods and modern teaching strategies. Their characteristics, methods of care and needs that differ from the needs of others and their special care methods and educational and guidance services that are compatible with their needs and characteristics have been clarified, which helps in developing their energies to the maximum extent permitted by their abilities and talents that their societies need. There is also a not insignificant percentage of gifted students with autism spectrum disorder who are distinguished by high intelligence, but due to the lack of awareness of the importance of caring for them and paying attention to them on the one hand, and the lack of awareness of some families of the characteristics of their gifted children with autism spectrum disorder on the other hand, which leads to focusing on the obvious weakness of their children and neglecting their high abilities, as well as the inability of specialists to detect and identify Gifted students with autism spectrum disorder due to the lack of measures and tools to detect them that suit their characteristics, which leads to the failure to develop and enhance their abilities, and the failure of society to benefit from these creative energies that need care and attention. Through this paper, the researcher recommended the necessity of paying attention to the category of gifted students with autism spectrum disorder and providing training programs for them and their families. As well as paying attention to the special needs and requirements of gifted students with autism spectrum disorder. And encouraging researchers to prepare tools for early detection and diagnosis of gifted students with autism spectrum disorder. And conducting training research for specialists to develop their abilities to detect early indicators of giftedness for students with autism spectrum disorder.